Presence of Fibromyalgia in Patients with Takayasu's Arteritis - ALİBAZ ÖNER, FATMA; MUMCU, GONCA; DİRESKENELİ, RAFİ HANER (JAPAN SOC INTERNAL MEDICINE, 2013)
Objective Data regarding the frequency of fibromyalgia (FM) in patients with Takayasu's arteritis (TAK) have not been previously reported. We aimed to investigate the frequency of FM in TAK, defined according to the new 2010 ACR Preliminary Diagnostic Criteria for Fibromyalgia. The association between the ACR-1990 and 2010 FM criteria and the effects of patient-reported outcomes (PROs) on FM were also analyzed. Methods We studied 55 patients (age: 42,30 +/- 12,37 years, F/M: 49/6) with TAK and 40 age-and sex-matched controls (age: 41 +/- 10.84 years, F/M: 31/9). All patients were examined for FM tender points by two observers and asked to complete the ACR 2010 FM questionnaire for FM. The SF-36, the Health Assessment Questionnaire (HAQ) and hospital anxiety and depression scales (HADS) were used to assess the quality of life. Thirty patients were reevaluated six months later. Results Seven (12.7%) patients with TAK and four patients with HC (10%) fulfilled the 2010 FM criteria (p=0.682), while three (5.4%) TAK patients and no controls (0%) met the 1990 criteria (p=0.133). FM was found at a significantly higher rate in the active patients than in the inactive patients according to the ACR-2010 FM criteria (p=0.006). The SF-36 physical component scores were significantly lower (p=0.003) and the HAQ scores were significantly higher in the TAK (p=0.006) patients than in the controls. Conclusion The frequency of FM is similar between the general population and patients with TAK. However, the incidence of FM is significantly higher in active patients. The new FM criteria subscales (WPI, SSS) are significantly correlated with scales such as the SF-36, anxiety and depression scales and HAQ in TAK patients, suggesting that, in a minority of patients with FM and TAK, PROs may be affected by the presence of FM.
Keywords: Takayasu arteritis; fibromyalgia; ACR FM criteria; disease activity; QUALITY-OF-LIFE; HEALTH-ASSESSMENT QUESTIONNAIRE; ANCA-ASSOCIATED VASCULITIS; RHEUMATOID-ARTHRITIS; DEPRESSION; CRITERIA; FATIGUE; ANXIETY; SCORES; PAIN